Mengoptimalkan Pertumbuhan Anak Usia Dini Melalui Penyuluhan Pemahaman Dampak Gadget di SD Plus Muhammadiyah Pancor - Saparwadi, Lalu (Welfare : Jurnal Pengabdian Masyarakat, 2023)
This activity aims to provide education to teachers and parents regarding the impact of gadget use in early childhood. The method applied in this service activity is counseling and presenting material by the service team in collaboration with Plus Muhammadiyah Pancor Elementary School. The results of this activity confirm that the role of parents is very crucial in supervising children's use of gadgets. Setting the duration of time and limiting access to features and applications on gadgets is also a very important step to prevent children from becoming too dependent on gadgets and to avoid exposure to material that is not appropriate for their age.